On the some subclasses of bi-univalent functions related to the Faber polynomial expansions and the Fibonacci numbers - Şahsene Altınkaya; Sibel Yalçın (Rendiconti di Matematica e delle Sue Applicazioni, 2020)
In this investigation, by using the Tremblay fractional derivative operator, we introduce a new class of bi-univalent functions based on the rule of subordination. Moreover, we use the Faber polynomial expansions and Fibonacci numbers to derive bounds for the general coefficient |an| of the bi-univalent function class